Emad M. Rasheed Effects of Some Garlic(Allium sativum) Preparations on The Sexual Behavior and Alcohol Toxicity in Mice - Emad . Rasheed (University of Thi-Qar Journal of Science, 2019)
This study was carried out to investigate the activities of crude, heated garlic and aged garlic extract in the testicular hypogonadism induced by warm water and alcohol toxicity .The results were showed that only crude garlic caused improvement of testicular function ,while the activity of warwed garlic did not improve this function with slight effect on the alcohol intoxication .The afficacy of aged garlic extract was significantly observed in two models.Theseresults can be concluded that the three garlic preparations have different pharmacological characters and the aged garlic extract could be the most effective preparation in the experimental models.